Impact of Real-World Problem-Solving Strategy on Biology Students’ Comprehension in Makurdi Metropolis - Helen Aladi Ogah; Ph. D Michael Terfa Angura; Ochanya Maryrose Nyinebi (Journal of Advanced Research in Education, 2025)
The study determined the impact of Real-World Problem-Solving Strategy (RWPSS) on biology students’ comprehension in Makurdi metropolis of Benue State, Nigeria. The study used quasi-experimental design. Three research questions and three hypotheses guided the study. The population of the study consisted of all students in the secondary schools in Makurdi metropolis with 90 as sample using Stratified random sampling technique from two schools. Biology Students Comprehension Test (BSCT) with 20 items constructed by the researcher which yielded a reliability coefficient of 0.80 and validated by one expert in Science Education and one in measurement and evaluation was used to collect data for the study. The data collected was analyzed using descriptive statistics of mean to answer the research questions while the t-test of independent sample was used to test the research hypotheses at 0.05 level of significance. The findings revealed among others that RWPSS is more effective in enhancing comprehension of biology students than CTM, recorded t-test value of 0.055 with a p-value of 0.040. This is less than 0.05 level of significance (p=0.040<0.05). RWPSS is more effective in enhancing the comprehension of male and female biology students than CTM, recorded t-test value of 0.055 with a p-value of 0.020. This is less than 0.05 level of significance (p=0.020<0.05). The study recommended among others that the Ministry of Education and School administrators should ensure that Real-world problem-solving strategy is used by teachers in enhancing comprehension of biology students irrespective of gender, boarding or day.